The Neurocognition Deployment Health Study: a prospective cohort study of Army Soldiers. - Vasterling JJ; Proctor SP; Amoroso P; Kane R; Gackstetter G; Ryan MAK; Friedman MJ; Vasterling, Jennifer J; Proctor, Susan P; Amoroso, Paul; Kane, Robert; Gackstetter, Gary; et al. (Military Medicine, 2006)
Questions remain regarding the effects of military operational deployment on health. The Neurocognition Deployment Health Study addresses several gaps in the deployment health literature, including lack of baseline health data, reliance on subjective measures of exposure and health variables, prolonged intervals between redeployment and health assessments, and lack of a uniform case definition. The Neurocognition Deployment Health Study uses a prospective cohort design to assess neuropsychological outcomes associated with Iraq deployment. Methods incorporate administration of performance-based neuropsychological measures to Army soldiers before and after Iraq deployment and to nondeployed Army Soldiers assessed during comparable periods of garrison duty. Findings should have the potential to delineate neuropsychological outcomes related to combat theater deployment and to identify potential risk and protective factors related to health outcomes.